Inovasi Pembelajaran Pendidikan Agama Islam dalam Era Industri 4.0 - Harimawan Harimawan; Arif Budi Rahardjo; Eko Harianto (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The development of Industry 4.0 is a challenge for the world of education, including Islamic religious education (PAI) learning. Teachers are required to be able to face more complex challenges. There are many complexities in the challenges of the industrial revolution 4.0 in the field of PAI learning. This research aims to find out about Islamic religious education learning innovations in industry 4.0 at SMK Muhammadiyah 1 Bantul. This research uses qualitative research methods which are delivered descriptively. PAI learning innovation is applied with the term "Kaizen" which comes from the Japanese concept of Continuous Incremental Improvement. Kaizen includes 5 stages that have the prefix "S", namely: Seiri, Seiton, Seiso, Seiketsu, and Shitsuke.